From Platonism to Neoplatonism - Merlan, Fr. author. aut Link
XIX, 250 p.
Keywords: The first edition of this book appeared in 1953; the second, revised and enlarged, in 1960. The present, third edition is essentially a reprint of the second, except for the correction of a few misprints and the following remarks, which refer to some recent publications* and replace the brief preface to the second edition. Neither Eudemus nor Theophrastus, so I said (p. 208£. ) knew a branch of theoretical philosophy the object of which would be something called 0'. 1 ~ 0'. 1 andwhich branch wouldbedistinct from theology. And there is no sign that they found such a branch (corresponding to what was later called metaphysica generalis) in Aristotle. To the names of Eudemus and Theophrastus we now can add that of Nicholas of Damascus. In 1965 H. J. Drossaart Lulofs published: Nicolaus Damascenus On the Philosophy of Aristotle (Leiden: Brill), Le. fragments of his m:pr. njc; 'ApLO''t'o't'&AOUC; qJLAOO'OqJLiXC; preserved in Syriac together with an English trans lation. In these fragments we find a competent presentation of Aristotle's theoretical philosophy, in systematic form. Nicholas subdivides Aristotle's theoretical philosophy into theology, physics, and mathematics and seems to be completely unaware of any additional branch of philosophy the object of which would be 0'. 1 ~ 0'. 1 distinct from theology with its object (the divine).